USER INTERFACE DESIGN, PERCEIVED EASE OF USE, ELECTRONIC WORD OF MOUTH, AND ONLINE ADVERTISING ON IMPULSIVE BUYING BEHAVIOR IN THE SHOPEE MARKETPLACE - Aswar, Nurul Fadilah (Journal Management & Economics Review (JUMPER), 2023)
This research aims to investigate the influence of interface design, perceived ease of use, electronic word of mouth, and online advertising on the impulsive buying behavior of students who use the Shopee application at the Faculty of Economics, Universitas Makassar. This study employs a quantitative method and a correlational approach that explains the causal relationships between variables through hypothesis testing. The research sample consists of 100 respondents selected through purposive sampling, characterized by being students studying at the Faculty of Economics, Universitas Negeri Makassar, and having made at least 5 transactions on Shopee. The data analysis conducted involves multiple linear regression analysis. The results of the study indicate that the interface design, perceived ease of use, electronic word of mouth, and online advertising significantly influence impulse buying. This suggests that students' impulsive buying behavior on the Shopee app is influenced by interface design, perceived ease of use, electronic word of mouth, and online advertising.